Religion and Change in Modern Britain - Bruce, Steve (Sociology of religion, 2013)
As with any edited collections, the quality of contributions to Linda Woodhead and Rebecca Catto's compendium is extremely variable, as is their application to the themes. Though Religion and Change in Modern Britain certainly contains a great deal of useful descriptive material on UK religion post-1945—the accounts of non-Christian religions are particularly good as are the details of important legal changes—and the extensive bibliographies are valuable, overall the volume falls short of its ambition of charting and explaining recent changes in the UK's religious landscape., One problem is the disciplinary background of the contributors.